Supporting PhD physicists through investigations of ethical decision-making and structures of graduate education - Bridges, Bill (My University, 2025)
The work represented in this dissertation is intended to support the development of PhD physicists in areas identified as critical to the PER community through established research in the community and from national reports, particularly in ethics education for faculty scientists and physics graduate education. I describe two individual projects that focus on considering different Epistemic Frames that faculty scientists engage in during value-laden discussions and the graduate education of physicists in terms of program requirements and retention measures. Scientists engage with ethical dilemmas regularly. Training modules are developed to instruct scientists to better identify and navigate these dilemmas, but often focus on rules and regulations and not contexts aligned with the needs of scientists. Case-based discussions have been shown to impact ethical decision-making, and part of the Goals and Values in Science project was to investigate the impact that value-laden discussions have on faculty scientists’ ethical decision-making. In this work, we applied the methodology of identifying epistemic frames to value-laden discussions. We identify three distinct group epistemic frames: Facilitator Frame, Sharing Science Frame, and Arguing Claims Frame. This work provides a foundation towards better understanding how faculty scientists make sense of value-laden discussions and promote productive avenues for designing ethical interventions. The number of PhDs awarded in physics since 1861 has dramatically expanded, sometimes rapidly. To fully understand the potentially diverse set of program requirements and expectations of physics graduate education, we investigated the structures of PhD-granting institutions in the United States. We determined 10 distinct structures of program requirements, including Core Courses, Elective Courses, Comprehensive Content Exams, Research Readiness Exams, The Dissertation, Supervisory Committee, Training, Annual Reports, The Teaching Assistant Requirement, and Presentations of Research. These structures represent the most common practices and requirements of the physics graduate programs investigated. We additionally identified a common narrative of physics graduate programs, the emphasis of physics content knowledge, and the diverse set of requirements for Candidacy Exams. The information from this study helps to support a foundation of current physics graduate program requirements and expectations, and how these structures could be further investigated to support students in physics graduate education. The rate of physics graduate students awarded a PhD has historically been near 50%, with no consistent way to measure retention and completion rates for individual institutions. We used graduate enrollment survey data from the American Institute of Physics between 2000 and 2022. We propose 2 sets of measures of graduate student retention and completion rates that are consistent for different institution sizes and degrees awarded, allowing us to calculate retention and completion rates at both the national level as well as the individual institutions. The Graduate Retention Rates consider the flux of graduate student populations. We applied measures to the National Set of data that totals information from all 284 graduate institutions and then applied to the individual Institutional Level. We determined a high retention rate with opportunities to further refine the measure of retention. We identified an increase in the completion rates of all degree types at the National Level.
Keywords: Physics education research; Physics graduate education; Ethics education for scientists